Between panegyrics and coins: a study of political culture through the rhetoric and the divine images in Tetrarchy - Zardini, Thiago Brandão (Romanitas - Revista de Estudos Grecolatinos, 2014)
The Tetrarchy’s reform and the systematic reordering of the imperial cult under the aegis of Diocletian and Maximian can be analyzed through the study of coins and the Latin Panegyrics. The purpose of this article is to understand the political role of these two elements, a priori considered as instruments of praise in the rituals of the basileia. As case study, we selected the images of Jupiter and especially of Hercules which are shown in the monetary issues and in some passages of the speeches. The bond between the basileus and the audience at the time of public rituals, as well as the power relations resulting from the legitimating of the monarchy will be analyzed in the light of the political culture.